Effect of Dietary Supplementation of Rumen Protected Methionine and Lysine on Immunity Status and Trace Mineral Profile in Sahiwal Female Calves - Rajwade, Neelkant; Kumari, Kiran; Archana; Pal, Prasanna; Gendley, M. K.; Gade, Nitin E.; Dubey, Meenu (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the months of May-June in 2018 at the Bull Mother Experimental Farm (BMEF), College of Veterinary Science & Animal Husbandry, Anjora, Durg, and the Government Cattle Breeding Farm (CBF), Anjora, Durg to evaluate the effect of dietary supplementation of rumen-protected methionine (RPM) and rumen protected lysine (RPL) on immunity status and trace mineral profile in indigenous Sahiwal female calves. Twenty calves aged 7–12 months with body weights ranging from 80 to 111 kg were randomly allotted into four groups (n=5 each): T1 (basal diet), T2 (basal diet+RPM 5 g day-1), T3 (basal diet+RPL 15 g day-1), and T4 (basal diet+RPM 5 g+RPL 15 g day-1) for a period of 90 days. Calves were maintained on a concentrate mixture and berseem hay (60:40 ratio) as per ICAR (2013) standards. Immunity was assessed using phytohaemagglutinin (PHA) skin test and lymphocyte proliferation assay, while serum concentrations of Fe, Cu, Zn, and Se were estimated by atomic absorption spectrophotometry. Results revealed no significant differences in PHA skin thickness or serum mineral concentrations among treatment groups, with values remaining within normal physiological ranges. However, RPM supplementation (T2) significantly improved lymphocyte proliferation (p≤0.05), indicating enhanced immune competence. These findings suggested that RPM could be considered a functional feed additive to strengthen immune responses in Sahiwal calves without altering mineral balance.